Journeys of Discovery in Voluntter Tourism: International Case Study Perspectives - Lyons, Kevin D (CABI, 2014)
fast-growing area of tourism. This book is organized into three parts that explore key approaches to, and dimensions of, volunteer tourism. In the opening chapter for each part we provide an in-depth discussion of relevant approaches and issues that link and frame the ensuing cases. Part I considers the perspectives of host communities and the organizations that provide them with volunteers as part of a process of social and community development. Part II presents case studies that focus upon the experiences of the volunteer tourist and considers issues of the self, motivation, identity and the impact of volunteer tourism upon the volunteer.